2020
DOI: 10.3390/jrfm13040083
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Transmissions and Volatility Spillovers between Global Price and U.S. Producer Price in Agricultural Markets

Abstract: A considerable number of studies have examined the relationship between global prices and local prices in food-importing nations, but the linkages between international prices and the producer prices of large agricultural exporters have been largely ignored. This paper analyzes the connections between world prices and U.S. producer prices in the wheat, soybeans, and corn markets using a vector error correction generalized autoregressive conditional heteroscedastic model with a multivariate Baba-Engle-Kraft Kro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Soybean is used not only as food but also as livestock feed. Since the United States is the second-largest soybean exporter to various nations such as China and Japan (Food and Agriculture Data, 2022), domestic meat prices in such importing countries could be affected by biofuel policies in the United States, as demonstrated by Guo and Tanaka (2020). The researchers proposed that the US farm-gate price of soybean significantly influences the international soybean price.…”
Section: F I G U R Ementioning
confidence: 99%
“…Soybean is used not only as food but also as livestock feed. Since the United States is the second-largest soybean exporter to various nations such as China and Japan (Food and Agriculture Data, 2022), domestic meat prices in such importing countries could be affected by biofuel policies in the United States, as demonstrated by Guo and Tanaka (2020). The researchers proposed that the US farm-gate price of soybean significantly influences the international soybean price.…”
Section: F I G U R Ementioning
confidence: 99%
“…Diantara berbagai studi yang melihat kaitan ataupun transmisi perubahan harga gabah di tingkat petani dengan perubahan harga beras di berbagai tingkat perdagangan, masih sedikit yang melakukan eksplorasi mengenai berapa lama transmisi perubahan harga gabah ke harga beras ataupun sebaliknya. Studi yang mempelajari kecepatan transmisi harga dilakukan oleh Guo & Tanaka (2020) yang menghasilkan informasi bahwa terdapat perbedaan kecepatan transmisi perubahan harga komoditas internasional terhadap komoditas pertanian di Cina. Studi lainnya dilakukan Chaudhary et al, (2019) terhadap besaran, kecepatan dan asimetri dari perdagangan beras pada tingkat grosir dan eceran di beberapa kota utama di Filipina.…”
Section: Pendahuluanunclassified
“…Coronado et al (2017) found that the causality among gold, crude oil, and U.S. stock markets goes in all directions, whereby gold and oil changes can be observed based upon U.S. stock market returns and vice versa. Most of the prior studies have focused on volatility spillovers (e.g., Hong et al 2009;Mensi et al 2018;Guo and Tanaka 2020) as opposed to price spillovers. Some studies focus solely on an individual set of asset prices (e.g., Marquez and Merler 2020).…”
Section: Introductionmentioning
confidence: 99%